Exploring the Effectiveness of Diversion Programs for Women Involved in Commercial Sex: A Comparison of Sex-Trafficked and Non-Trafficked Individuals - Noam Haviv; Dominique Roe-Sepowitz (Social Sciences, 2025)
Diversion programs are increasingly used as alternatives to criminal penalties for women involved in commercial sex, yet limited research has examined how such programs support behavior change across diverse subgroups, particularly between sex-trafficked and non-trafficked participants. This study evaluates changes in readiness for change among 131 women who participated in a court-ordered diversion program led by survivors of sex trafficking. Participants were classified as sex-trafficked or non-trafficked based on self-reported age of entry and experiences of third-party control. The program offered a range of trauma-informed services aimed at fostering holistic well-being and facilitating a pathway out of sex trafficking and prostitution. Participants engaged in group classes focused on job interview skills, emotion regulation, substance use awareness, and psychoeducation related to trauma. Life skills workshops addressed financial literacy, relationship dynamics, and conflict resolution. In addition, participants received referrals to GED programs, career training, mental health services, and emergency housing as needed. Program duration typically ranged from 12 to 16 weeks, adjusted for individual needs. Results from a repeated-measures Analysis of Variance (ANOVA) revealed a significant increase in readiness for change (p < 0.05) from program entry to completion. However, women with trafficking histories demonstrated smaller gains than their non-trafficked peers, suggesting that trauma-related and systemic barriers may limit the impact of short-term interventions. These findings underscore the importance of tailoring diversion programs to address the complex needs of sex-trafficked individuals and support the development of differentiated trauma-responsive strategies within diversion frameworks.